Makna dan Pemahaman Orang Tua dalam Mendidik Anak Usia Dini (Studi Kualitatif pada Orang Tua di PAUD Al-Ansor Bina Bangsa) - Purwaningsih, Nining (Al-DYAS, 2025)
This study is motivated by the limited research on the meaning and understanding parents hold regarding early childhood education, despite its significant impact on character development and the effectiveness of early childhood education programs. The objective of this research is to deeply explore how parents perceive and understand their roles in educating young children, particularly in navigating the challenges of parenting in the digital era. Employing a qualitative approach with an intrinsic case study design, the study involved four parents of students at PAUD Al-Ansor Bina Bangsa, selected through purposive sampling. Data were collected using semi-structured interviews, participatory observation, and documentation, and analyzed thematically. The findings reveal that parents perceive their roles as guides, mentors, and role models, carried out through emotional involvement and spiritual closeness. These findings reinforce the relevance of parental involvement theory and the authoritative parenting style, which emphasizes a balance between responsiveness and structure in early childhood education. The main conclusion is that parental involvement in child-rearing is not merely a functional act, but a reflective process that integrates value awareness, emotional connection, and moral responsibility. The study offers theoretical contributions to the literature on the meaning of parenting and practical recommendations for early childhood education institutions and policymakers to strengthen parenting programs grounded in reflection, values, and active support amid the challenges of the digital age.